PERCEPTIONS OF AFRICAN AMERICANS IN OBTAINING FACULTY POSITIONS IN HIGHER EDUCATION HOSPITALITY PROGRAMS - Hill, Brian J (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
This article aims to bring to light the racial imbalance in hiring faculty staff in higher education hospitality programs. Though one in five positions are held by ethnic and racial minorities across the field of higher education, women and minority groups hold fewer positions of leadership in comparison to their White male counterparts. The number of Ph.D. graduates, especially African Americans, is not commensurate to the hired assistant professors, signifying the failure to weigh diversity in the hiring processes. However, there have been programs aimed at achieving better minority representation across, with a focus on both lower and executive positions.